Research on Pull-out Mechanical Characteristics of Pile Foundation in Submerged Floating Tunnel. (2016) - Jiang, Xinghong; Li, Ke
Abstract: The submerged floating tunnel is a new tunnel type, with complex structure and requiring high construction demands. While it has been theoretically researched for a long period of time, there is no application example. The uplift pile, with fatal research significance, is the structure foundation of a floating tunnel. The paper starts with the cable arrangement form of floating tunnels and gives an analysis on the force-bearing characteristics of pile foundation in the submerged floating tunnels; it integrates numerical simulation to analysis the characteristics of the bearing capacity of pile foundations changing with displacement curve (Q-S curve) under different inclinations. The soil deformation in the limit state of bearing capacity, the distribution of plastic failure zone and their relative causes are analyzed. The paper acquires the envelope curve of bearing capacity under the displacement effect of different inclinations, as well as the conclusion that 30° is a suitable temperature for cable arrangement. The research achievement has a certain guiding significance for the cable arrangement angle setting of floating tunnels and the reinforcement treatment of pile foundation.